Depthmap: A forward-looking approach to urban planning for the future of new cities Case study of the new city Ali Mendjeli in Constantine - Algeria - عساسي عبدالحليم; بن مشيرح جمعة; سامعي رشيدة (Journal of Architecture and environment of child, 2020)
This paper explain how specially the space type can interpret why the human being derives to a negative behavior like "Crime". So, in this study we adopt the visibility approach which is developed by the laboratory of space syntax (UCL), and which makes a sense for the link between the space design and its use and its positive or negative social consequences in the future. Then, the purpose of this paper is to present the importance of the use of visibility map which can also be an outlook approach for detecting potential hot-spots in urban planning designs specially of new cities, for avoiding the negative using of urban spaces like "Crime" in the future. The case of study is the new city of Ali Mendjeli (Constantine - Algeria), the capital of the East of Algeria known by a very fast demographic and urban growth. After analyzing a central urban neighborhood of this city using Depthmap, we found thirty-four hot-spots which can be appropriate spaces for the exercise of crime in the future, and we found that this point was downplayed in the urban planning designs before the realization of Ali Mendjeli new city. Keywords : Vision ; Software ; Urban planning ; Forward-looking ; New cities.